I–III AD Estimating Finds in the Forest-Steppe Sites of the Tobol and Irtysh Rivers Basin - Svetlana V. Sharapova; Vladimir Yu. Malashev (Нижневолжский археологический вестник, 2022)
The article deals with artifacts found in the Iron Age kurgans over the Trans-Uralian and West Siberian forest-steppe, which might be referencing for chronology of the Sargat culture and late complexes emerging within area under study. Our emphasis is placed on the analyses of some belt and strap fittings. Meanwhile the novelty of undertaken research might be viewed less in general discussion of chronological aspects but it brings to light quite rare examples of metal belt buckles among the well-known collections. Such finds broad our knowledge on material culture of the forest-steppe population during the first centuries AD and allow the authors’ assume on origin and time of appearance of buckles with flexile tongue as items of Roman patterns. At the same time one may presume that emergence of belt fittings with such construction over the vast territory, i.e. on the south of Eastern Europe on the one side and Central Asia and Siberia on the other side could occur irrespectively in general. In chronological aspect the introduction of buckles with flexile tongue into Asiatic territory of the steppe belt could have been no earlier than during the second half of the first century AD. Based on archaeological finds from the latest complexes the highest chronological edge of the Sargat culture might be considered as not beyond the mid of the third century AD. The early third century BC marks decline and stagnation of the culture, and archaeological sites with main, blatant features dated back to the mid of the third century AD are not found in the forest-steppe eastward the Urals. All available data testify to the fact that a relatively short-term lacuna divides archaeological materials of the early Iron Age and Great Folk Movement.